Laboratory-scale smelting of copper-anode slimes - G. G. Barbante (The Institute of Materials, Minerals and Mining, 1995)
Anode slimes produced during copper electrorefining are a valuable source of silver, gold, selenium and tellurium. The conventional pyrometallurgical process for treating slimes involves preliminary leaching in sulphuric acid followed by smelting in a reverberatory furnace with fluxes, but it is slow and has many recycle streams. The chemistry of the phases and the reactions that occur in slimes smelting are poorly understood and and this prevents major improvements to the process. Laboratory-scale experiments were conducted using unleached slimes, with and without the addition of fluxes and under neutral, oxidising and reducing conditions. Results show that selenium is readily removed as gaseous selenium dioxide and that molten Cu-Ag-Se-O phases form when fluxes are added. Oxidation-refining of these phases by air injection and flux addition can result in the formation of silver suitable for further electrorefining